A Clash of Norms? How Reciprocity and International Humanitarian Law affect American Opinion on the Treatment of POWs. (May 2019) - Chu, Jonathan A.
Reciprocity is one of the oldest principles of warfare, but humanitarian norms embedded in international humanitarian law (IHL) prohibit reciprocity over various wartime acts. When it comes to the treatment of prisoners of war (POWs), how do these conflicting norms shape public opinion? One perspective is that citizens who learn about IHL acquire an unconditional aversion to abusing POWs. Alternatively, people may understand IHL as a conditional commitment that instead strengthens their approval for reciprocal conduct. Survey experiments fielded in the United States support the latter view: people's preferences depend on the enemy's behavior, and this "reciprocity effect" is largest among those who believe that the United States is legally committed to treating POWs humanely. Puzzlingly, prior studies do not find a reciprocity effect, but this is due to their use of a no-information experimental control group, which led to a lack of control over the subjects' assumptions about the survey.